Dissolved Methane Transport in the Tatar Strait and the Deepest Basin of the Japan (East) Sea from Its Possible Sources - Andrei Kholmogorov; Vladimir Ponomarev; Nadezhda Syrbu; Svetlana Shkorba (Water, 2023)
Dissolved methane coming from its various sources is an important component of seawater. Finding these probable sources allows for the determination of potential oil and/or gas deposit areas. From an ecological point of view, methane transport studies can reveal probable pollution areas on the one hand and biological communities, being the lower part of the food chain commercial species, on the other hand. Moreover, the methane transport mechanism can help to obtain a better understanding of the contribution of the World’s oceans to global greenhouse gas emissions. Our research combines gas geochemistry and oceanography. In comparing the research results of both branches, we show the mechanism of methane transport. The features of the dissolved methane on oceanographic sections in the southern part of the Tatar Strait are discussed. The CH4 intake from the bottom sediment and the transport of dissolved methane by the currents in the Tatar Strait are shown. The absolute maximum concentration of CH4 (155.6 nM/L) was observed on the western Sakhalin Island shelf at the near-bottom layer at a depth of 65 m. The local maximum, 84.4 nM/L, was found north of the absolute maximum in the jet current under the seasonal pycnocline. A comparison of the simulated surface seawater origin and dissolved methane in the 4 m depth distribution shows methane transport with the currents in the Tatar Strait. Another studied section is along 134° E in the Japan Basin of the Japan (East) Sea. Here, the East Korean Warm Current close to the Yamato Rise slope and a quasi-stationary mesoscale anticyclonic eddy centered at 41° N intersect. The local maximum methane concentration of 8.2 nM/L is also observed under the seasonal pycnocline. In a mesoscale anticyclonic eddy at 134° E in the deep part of the Japan Basin, a local methane maximum of 5.2 nM/L is detected under the seasonal pycnocline as well.